Financial accounting applications 2 - Carr, Peter (Peter W.); Pascoe, Ian. (Melbourne : Nelson, 1994)
This book is divided into six parts: Accounting for and control over inventories; Accounting for partnership; Primary producers; Leases; Accounting records for consignments; and Accounting for investments.
Keywords: Accounting; Economics; Accounting; Accounting -- Problems, exercises, etc